Combining postgraduate research training, public engagement, and primary school science education—a Superbugs Master (MSc) class - Tyrrell, Jonathan Mark; Ayanikkad, Haritha Udayan; Nalleppillil-Gopakumar, Vasudev; Oyebode, Rachel; Nnamdi Blessing, Chiamaka; Hatch, Sarah; Eberl, Matthias (Frontiers in Microbiology, 2024)
Since 2018, the 'Superbugs' initiative at Cardiff University (United Kingdom) has been delivering projects that take a research-driven approach to public engagement, involving rigorous evaluation of the methodologies of delivery and the mechanics of communication. The overall aim of Superbugs is to raise awareness and improve public knowledge of microbiology, infection and antimicrobial resistance (AMR). In the present project, four postgraduate students were recruited to undertake research projects as part of their Master of Science (MSc) studies. After a period of literature appraisals, the students chose to focus on the topic of personal and food hygiene and were tasked with collecting information on effective strategies for educating young children. Taking advantage of a focus group of primary school teachers, the students then designed evidence-informed educational activities and the evaluation strategies by which the impact of these would be assessed. A pilot delivery of these activities was carried out in a community setting at a local public library, before final delivery as part of a school outreach workshop. The MSc students produced three new elements of educational material; a story book, a treasure hunt and an interactive card game, primarily built around the concepts of challenge and gamification. Feedback collected from primary school pupils aged 6-7 years old and teachers indicated that the activities developed were successful in both being engaging to young people and resulting in an improved knowledge on the chosen topics. Taken together, we present pilot evidence that postgraduate research training, underpinned by active and service learning, represent a valid and effective way of delivering impactful public engagement. In turn, the experience holds benefit for the students not only in terms of their academic study and core scientific skills, but also their wider appreciation and confidence in being effective engagers and science communicators.